2021
DOI: 10.3389/fpsyg.2021.628342
|View full text |Cite
|
Sign up to set email alerts
|

Similarity Effect and Purchase Behavior of Organic Food Under the Mediating Role of Perceived Values in the Context of COVID-19

Abstract: Due to the influence of COVID-19, people pay more attention to the balance between human and nature and pursue more healthy, environmental and nutritional sustainable products (such as organic food). However, the mainstream consumption of organic food is far less, especially in developing countries like China. Therefore, it is urgent to take effective measures to promote the development of China's organic food market. This current study investigated the relationships between consumers' similarity (i.e., inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(45 citation statements)
references
References 90 publications
(130 reference statements)
1
30
0
4
Order By: Relevance
“…The findings provide new insights into PKM, where clearly informing consumers about the health and environmental benefits of organic products can undermine skepticism and increase persuasion. Therefore, organic producers and retailers should use the most authoritative scientific evidence (e.g., Organic food certification system; Wei et al, 2022 ) and formulate corresponding strategies to promote consumers’ understanding of organic information (such as social media publicity; Liu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings provide new insights into PKM, where clearly informing consumers about the health and environmental benefits of organic products can undermine skepticism and increase persuasion. Therefore, organic producers and retailers should use the most authoritative scientific evidence (e.g., Organic food certification system; Wei et al, 2022 ) and formulate corresponding strategies to promote consumers’ understanding of organic information (such as social media publicity; Liu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the advantages of organic food production, consumer appreciation, and consumer purchase propensity in surveys ( Rana and Paul, 2017 ; Wang et al, 2021 ), its market share is less than 5% in most countries ( Hansmann et al, 2020 ), and only 0.8% in China ( China National Commercial Information Center, 2019 ; FiBL, and IFOAM, 2020 ). A significant gap exists between their willingness to buy and actual consumption ( Carrington et al, 2014 ; Massey et al, 2018 ) because consumers neither realize nor believe in the claimed benefits of organic products ( Van Doorn and Verhoef, 2015 ; Liu et al, 2021 ) or their high prices ( Katt and Meixner, 2020 ). The gap is even more pronounced in the hospitality ( Juvan and Dolnicar, 2014 ; Konuk, 2019 ) and when it comes to paying for organic food in restaurants ( Jeong and Jang, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the state of uncertainty, consumers similarly become also extra anxious and sensitive about collecting more information related Coronavirus causes and consequences therefore, they are forced to reevaluate their habits and actions. As time goes on, consumers may have information anxiety in common; getting the similar information through various media every day, people would find that they have common information anxiety characteristics which is proved to affect the organic purchase behavior (Liu et al, 2021). Ruiz Mafé and Sanz Blas (2009) found that the information that consumers are exposed to through various information channels can affect their perceived values and behavior.…”
Section: Information Anxietymentioning
confidence: 99%
“…Specifically, in 2018, the consumption of organic food in China accounted for only 8.3% of global organic food consumption (Willer & Lernoud, 2020). The per capita consumption of organic food is only 5.8 euros, less than half of the global per capita consumption (Liu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%